How to promote attentional efficacy and cognitive control processes: Experience in argentine school children - Ison, Mirta Susana (2020)
Attention is one of the cognitive control processes that are clearly relevant for socio-cognitive performance and young childrens school learning. Good attention functioning is one of the important predictors of cognitive level in childhood. Although there is no unified theory of attention, current neurocognitive models have agreed to define it as a cognitive control function responsible for the hierarchical organization of the processes in charge of elaborating information. The capacity of attention can be modified with continuous practice. For this reason, its strengthening in childhood could favour the development of the functioning of cognitive control processes in later years. This article presents two programs for the attention and sociocognitive strengthening in children of pre-elementary and elementary school level, in the province of Mendoza, Argentina. This study provides empirical evidence of the effectiveness of training programs applied in the school context and of therelevance of the involvement of parents and educators.